PENGARUH INTELLECTUAL CAPITAL TERHADAP KINERJA KEUANGAN BANK SYARIAH DI INDONESIA - Krisna Jesica Anggriyanti; Muchamad Syafruddin (Diponegoro Journal of Accounting, 2021)
This study aims to empirically investigate the impact of intellectual capital (IC) on the financialperformance of Islamic Banks operating in Indonesia. The variables used in this study are the dependent variable (financial performance), the independent variables (value added intellectual capital, capital employed efficiency, human capital efficiency, and structural capital efficiency) and the control variables (Leverage and Size).The population in this study is Islamic Banks listed website OJK in 2017-2019. Sampling is done by purposive sampling. Based on the purposive sampling method, samples obtained were 33 samplesfor the three years obtained (2017-2019). The analytical method used in this study is ordinary leastsquare (OLS).The results of this study indicate that value added intellectual capital, capital employed efficiency, and human capital have a positive and significant effect on financial performance. While,structural capital efficiency has a negative but significantly influence the financial performance.